A Study On Road Safety Awareness And Practices Among University Students - Muhammad Syafiq Amirul, Shaari (2025)
Road safety is a critical issue worldwide, with road accidents posing significant public health concerns, particularly among younger populations. This study aims to assess the levels of road safety knowledge, awareness, and practices among university students. A cross-sectional analytical design was employed, targeting 269 undergraduate students from the Faculty of Industrial Science and Technology at University Malaysia Pahang Al-Sultan Abdullah. Data were collected through a validated questionnaire addressing road safety knowledge, awareness, and practices, and analyzed using descriptive statistics and Spearman's correlation. The findings revealed that the overall level of road safety knowledge among respondents was high, with an average score of 87.3%. Similarly, road safety awareness and road safety practices were also categorized as high, with an average mean score of 4.12 and 3.97.